Type 2 Diabetes, Obesity, and Cancer Share Some Common and Critical Pathways - Rahman, Ishrat; Athar, Md Tanwir; Islam, Mozaffarul (Frontiers in Oncology, 2021)
Diabetes and cancer are among the most frequent and complex diseases. Epidemiological evidence showed that the patients suffering from diabetes are significantly at higher risk for a number of cancer types. There are a number of evidence that supports the hypothesis that these diseases are interlinked and obesity may aggravate the risk(s) of type 2 diabetes and cancer. Multi-level unwanted alterations such as (epi-)genetic alterations, changes at the transcriptional level, and altered signaling pathways (receptor, cytoplasmic, and nuclear level) are the major source which promotes a number of complex diseases and such heterogeneous level of complexities are considered as the major barrier in the development of therapeutic. With so many known challenges, it is critical to understand the relationships and the common shared causes between type 2 diabetes and cancer, which is difficult to unravel and understand. Furthermore, the real complexity arises during diagnosis from contended corroborations that specific drug(s) (individually or in combination) during the diagnosis process of type 2 diabetes may increase or decrease the cancer risk or affect cancer prognosis. In this review article, we have presented the recent and most updated evidence from the studies where the origin, biological background, the correlation between them have been presented or proved. Furthermore, we have summarized the methodological challenges and tasks that are frequently encountered. We have also outlined the physiological links between type 2 diabetes and cancers. Finally, we have presented and summarized the outline of the hallmarks for both these diseases, diabetes and cancer.